The Effect of the T.A.S.C. Model on Developing the Skill Performance of Ornamentation Art among Secondary School Female Students in Art Education (Journal of the College of Basic Education, 2026)
The current research aims to identify the effect of the T.A.S.C. model on developing the skill performance of ornamentation art among secondary school female students in the subject of Art Education.Theresearch populatio consisted of fifth-grade scientific and literary female students in morning study for the academic year 2025–2026 in secondary and preparatory schools for girls in Baghdad / General Directorate of Education of Al-Rusafa First. The research sample consisted of fifth-grade scientific female students from Al-Fawz Secondary School for Girls, totaling 64 students, distributed into 32 students for the experimental group and 32 students for the control group.The research require thepreparation of an instructional unit in Islamic ornamentation art, as well as the preparation of six lesson plan acognitive achievement test consisting of 20 multiple-choice items was developed, in addition to a skill test consisting of two questions. A skill performance evaluation form was also prepared, consisting of 12 items. After applying the statistical methods, the researcher reached the following results the students of experimental group outperformed the students of the control group in both the post skill test and the post cognitive achievement test, which confirms the effectiveness of theT.A.S.C model in developing skill performance and cognitive achievement.The researcher recommended that Art Education teachers adopt the T.A.S.C. model in teaching.Theresearcher alsosuggested conducting astudy to identify the effectiveness of the T.A.S.C model in developing artistic skills in the subject of arts and crafts.